The role of the diaspora for the recovery of Ukraine - Joop Adema; Yvonne Giesing; T. V. Panécenko; Panu Poutvaara (EconPol Forum, 2023)
Ukraine has a long history of emigration and a large diaspora in high-income countries.This diaspora has supported democratic and economic development before and during the war. Remittances corresponded to 7 percent of Ukraine's GDP in 2021. Return migration will be an essential factor for the reconstruction of Ukraine. Well-integrated Ukrainian emigrants can help to integrate Ukraine into the European Union
Keywords: 330